CODE-MIXING USAGE IN FATHIA IZZATI’S YOUTUBE CHANNEL VIDEO - Arnila Septia Cahaya; Eva Nurchurifiani; Innayah Hanum; Maria Lovelita Vinantiastuti (Universitas Pamulang, 2023)
Sociolinguistics considers code mixing as an important area of study, particularly as a sign of bilingualism, where individuals use more than one language. Code-mixing transpires when individuals integrate different languages in their speech or sentences. The objective of this investigation is to recognize the varieties and motivations behind code-mixing as evidenced in a YouTube video by Fathia Izzati. The study employs a descriptive qualitative approach to showcase the findings derived from the analysis of the data. In order to classify the forms of code-mixing, specifically intra-sentential, intra-lexical, and those involving a shift in pronunciation, the researchers utilize Hoffman's theory. The subject data consists of Fathia Izzati's utterances in a video titled